2015
DOI: 10.18632/oncotarget.3925
|View full text |Cite
|
Sign up to set email alerts
|

Detecting predictive androgen receptor modifications in circulating prostate cancer cells

Abstract: Molecular modifications of the androgen receptor (AR) can cause resistance to androgen deprivation therapy (ADT) in prostate cancer patients. Since lack of representative tumor samples hinders therapy adjustments according to emerging AR-modifications, we evaluated simultaneous detection of the two most common AR modifications (AR-V7 splice variant and AR point mutations) in circulating tumor cells (CTCs). We devised a single-tube assay to detect AR-V7 splice variants and AR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 29 publications
(25 reference statements)
9
86
1
Order By: Relevance
“…Some studies remark the role of molecular modifications that cause resistance to androgen deprivation therapy, mainly in the AR [26]. Other studies demonstrate the effectiveness of PCA3, PSGR (OR51E2), and PSMA (FOLH1) expression levels in urine sediment as biomarkers for the detection of PCa in benign prostatic hyperplasia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies remark the role of molecular modifications that cause resistance to androgen deprivation therapy, mainly in the AR [26]. Other studies demonstrate the effectiveness of PCA3, PSGR (OR51E2), and PSMA (FOLH1) expression levels in urine sediment as biomarkers for the detection of PCa in benign prostatic hyperplasia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Mutations or amplification of the AR can cause resistance to androgen-deprivation therapy and are detectable in CTCs [145]. Moreover, recent studies have shown that mRNA expression of AR-V7, a truncated mRNA splice variant of AR that lacks the ligand-binding domain but remains constitutively active, in CTCs may predict failure of treatment with enzalutamide and abiraterone [146,147], but retained sensitivity to cytotoxic taxanes such as docetaxel [81,[148][149][150]. In addition, a point mutation (F876L) in the ligand-binding domain of AR confers resistance to enzalutamide [151,152].…”
Section: Therapeutic Targets and Resistance Mechanismsmentioning
confidence: 99%
“…Also, median PFS, clinical or radiographic PFS, and median OS were significantly lower in the AR-V7-positive group as compared to the AR-V7-negative group. However, these data need external validation in a larger cohort of patients since a recently published study reported a 10% response rate to AA/P or ENZ in AR-V7-positive patients [73]. …”
Section: Mechanisms Of Resistance and Sequencing Treatment Strategiesmentioning
confidence: 99%